(3GdJShjb GdOhdjs ((3GdbGgQI(B:s (3GdefXeI GdYQHjI ddJfejI GdGOGQjI(B,s, 2007)
(3efXeI GdJLGQI GdOhdjI , GdGdOhd GdYQHjI GdMbhb hGdGdJRGeGJ efXeI GdJLGQI GdYGdejI , egfjI GdJShjb aj Xd GdYhdeI GdGbJUGOjI , JfejI GdGTgGQ aj GdCShGb GdYGdejI , GdJShjb GdOhdj aj Xd GdYhdeI GdNUGFU hGdeHGOF , GdJYQaQ Ydi eOi LGgRjI GdeDSSGJ GdYQHjI dJUOjQ efJhLGJgG Edi GdCShGb GdYGdejI , JTNjU GdJUOjQ HGdeDSSI hJMdjd GdHjFI GdNGQLjI hOhQgeG aj JMOjO CSJQGJLjI ZR GdCShGb GdOhdjI , GdHYO GdCNdGbj aj GdJShjb GdYGdej , GdJLGQI GdEdcJQhfjI hJMSjf GdebOQI GdJfGaSjI ddeDSSGJ GdeUOQI JLQHI eLehYI TQcGJ ahGR GdMcjQ hTQcGg, CKQ GdGHJcGQ GdJShjbj aj LhOI GdNOeGJ GdeUQajIs
(3HjHdjhZQGajG U(B.270s
Keywords: (3JShjb Ohdjs; (3JUOjQs; (3YhdeIs; (3egfjI GdJShjbs